Infective capacity of arbuscular mycorrhizal fungi in reforested areas after bauxite mining in the Pará State, Brazil - Caproni, Ana Lucy; Franco, Avílio Antônio; Berbara, Ricardo Luis Louro; Granha, José Rodolfo Dantas de Oliveira; Ribeiro, Eliane Maria da Silva; Júnior, Orivaldo José Saggin (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the infective capacity of arbuscular mycorrhizal fungi (AMF) species and relate it to the most probable number (MPN) of infective propagules and number of spores extracted directly from the field. Soil samples were taken from areas degraded by bauxite mining, 2, 6, 12 and 16 years after reforestation and from an area of primary forest. The spores were extracted and morphologically identified. Most of the species had different behavior for the areas of study. Glomus macrocarpum showed fast infectivity in soils with high infective potential, independently of the soil origin. This species also showed high MPN values of infective propagules and high number of spores in all areas. The infective capacity of the species did not relate to the density of infective propagules. AMF species have different degrees of tolerance to the soil conditions and they behaved in different ways, according to the age of the revegetation.